Compostagem de lodo de uma estação de tratamento de efluentes sanitários - Pereira, Heron da Silva (2018)
Due to the development of environmental technologies, sewage and effluent treatment has become increasingly efficient in the removal of pollutants. As a result, loads of xenobiotics are removed from the wastewater. In another words, a greater amount of sludge is removed from the effluent. This sludge has distinct characteristics, varying in region and type of sewage treatment, moreover, it has potential to be reused as organic fertilizers. However, in order to be used for this purpose, sewage sludge needs to pass over a process of elimination of pathogens and stabilization of other physical-chemical parameters, and composting is a technique that makes this treatment viable. The purpose of this dissertation was to evaluate the composting process of a sewage treatment plant, in order to obtain a compost that complies with current legislation to be used in agricultural soil. Four treatments were tested: T1- Aerobic sludge + wood shaving; T2- Aerobic sludge + wood shaving + monzogranite; T3- Aerobic sludge + wood shavings + sugarcane bagasse; T4- Aerobic sludge + sugarcane bagasse + monzogranite. The composting lasted 90 days and the main physical-chemical parameters described in the Brazilian legislation were analyzed. The study showed that sugarcane bagasse and monzogranite improved composting, and that all treatments had significant removal of pathogens established in CONAMA Resolution No. 375/2006. However, the process did not comply with CONAMA Resolution No. 481/2017 in terms of temperatures.